Solve for x
x=\frac{\sqrt{105}}{12}-\frac{1}{4}\approx 0.603912564
x=-\frac{\sqrt{105}}{12}-\frac{1}{4}\approx -1.103912564
Graph
Share
Copied to clipboard
2\left(5-3x^{2}\right)-12x=3\left(2-3x\right)
Multiply both sides of the equation by 12, the least common multiple of 6,4.
10-6x^{2}-12x=3\left(2-3x\right)
Use the distributive property to multiply 2 by 5-3x^{2}.
10-6x^{2}-12x=6-9x
Use the distributive property to multiply 3 by 2-3x.
10-6x^{2}-12x-6=-9x
Subtract 6 from both sides.
4-6x^{2}-12x=-9x
Subtract 6 from 10 to get 4.
4-6x^{2}-12x+9x=0
Add 9x to both sides.
4-6x^{2}-3x=0
Combine -12x and 9x to get -3x.
-6x^{2}-3x+4=0
All equations of the form ax^{2}+bx+c=0 can be solved using the quadratic formula: \frac{-b±\sqrt{b^{2}-4ac}}{2a}. The quadratic formula gives two solutions, one when ± is addition and one when it is subtraction.
x=\frac{-\left(-3\right)±\sqrt{\left(-3\right)^{2}-4\left(-6\right)\times 4}}{2\left(-6\right)}
This equation is in standard form: ax^{2}+bx+c=0. Substitute -6 for a, -3 for b, and 4 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
x=\frac{-\left(-3\right)±\sqrt{9-4\left(-6\right)\times 4}}{2\left(-6\right)}
Square -3.
x=\frac{-\left(-3\right)±\sqrt{9+24\times 4}}{2\left(-6\right)}
Multiply -4 times -6.
x=\frac{-\left(-3\right)±\sqrt{9+96}}{2\left(-6\right)}
Multiply 24 times 4.
x=\frac{-\left(-3\right)±\sqrt{105}}{2\left(-6\right)}
Add 9 to 96.
x=\frac{3±\sqrt{105}}{2\left(-6\right)}
The opposite of -3 is 3.
x=\frac{3±\sqrt{105}}{-12}
Multiply 2 times -6.
x=\frac{\sqrt{105}+3}{-12}
Now solve the equation x=\frac{3±\sqrt{105}}{-12} when ± is plus. Add 3 to \sqrt{105}.
x=-\frac{\sqrt{105}}{12}-\frac{1}{4}
Divide 3+\sqrt{105} by -12.
x=\frac{3-\sqrt{105}}{-12}
Now solve the equation x=\frac{3±\sqrt{105}}{-12} when ± is minus. Subtract \sqrt{105} from 3.
x=\frac{\sqrt{105}}{12}-\frac{1}{4}
Divide 3-\sqrt{105} by -12.
x=-\frac{\sqrt{105}}{12}-\frac{1}{4} x=\frac{\sqrt{105}}{12}-\frac{1}{4}
The equation is now solved.
2\left(5-3x^{2}\right)-12x=3\left(2-3x\right)
Multiply both sides of the equation by 12, the least common multiple of 6,4.
10-6x^{2}-12x=3\left(2-3x\right)
Use the distributive property to multiply 2 by 5-3x^{2}.
10-6x^{2}-12x=6-9x
Use the distributive property to multiply 3 by 2-3x.
10-6x^{2}-12x+9x=6
Add 9x to both sides.
10-6x^{2}-3x=6
Combine -12x and 9x to get -3x.
-6x^{2}-3x=6-10
Subtract 10 from both sides.
-6x^{2}-3x=-4
Subtract 10 from 6 to get -4.
\frac{-6x^{2}-3x}{-6}=-\frac{4}{-6}
Divide both sides by -6.
x^{2}+\left(-\frac{3}{-6}\right)x=-\frac{4}{-6}
Dividing by -6 undoes the multiplication by -6.
x^{2}+\frac{1}{2}x=-\frac{4}{-6}
Reduce the fraction \frac{-3}{-6} to lowest terms by extracting and canceling out 3.
x^{2}+\frac{1}{2}x=\frac{2}{3}
Reduce the fraction \frac{-4}{-6} to lowest terms by extracting and canceling out 2.
x^{2}+\frac{1}{2}x+\left(\frac{1}{4}\right)^{2}=\frac{2}{3}+\left(\frac{1}{4}\right)^{2}
Divide \frac{1}{2}, the coefficient of the x term, by 2 to get \frac{1}{4}. Then add the square of \frac{1}{4} to both sides of the equation. This step makes the left hand side of the equation a perfect square.
x^{2}+\frac{1}{2}x+\frac{1}{16}=\frac{2}{3}+\frac{1}{16}
Square \frac{1}{4} by squaring both the numerator and the denominator of the fraction.
x^{2}+\frac{1}{2}x+\frac{1}{16}=\frac{35}{48}
Add \frac{2}{3} to \frac{1}{16} by finding a common denominator and adding the numerators. Then reduce the fraction to lowest terms if possible.
\left(x+\frac{1}{4}\right)^{2}=\frac{35}{48}
Factor x^{2}+\frac{1}{2}x+\frac{1}{16}. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(x+\frac{1}{4}\right)^{2}}=\sqrt{\frac{35}{48}}
Take the square root of both sides of the equation.
x+\frac{1}{4}=\frac{\sqrt{105}}{12} x+\frac{1}{4}=-\frac{\sqrt{105}}{12}
Simplify.
x=\frac{\sqrt{105}}{12}-\frac{1}{4} x=-\frac{\sqrt{105}}{12}-\frac{1}{4}
Subtract \frac{1}{4} from both sides of the equation.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}